CRITICAL SUCCESS FACTORS FOR MODULAR CONSTRUCTION ON HIGH-RISE RESIDENTIAL BUILDINGS BASED RISK MANAGEABILITY TO INCREASE PROJECT TIME PERFORMANCE - Dinal Aulia; Vian Marantha Haryanto; Agung Barokah Waseso; Endarmadi Aji Prayitno; Mira Marindaa T Sampetoding (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2023)
International Construction Costs published in Comparison 2020 continued to increase as an impact of the Covid-19 pandemic, The modular system is considered able to answer the problems of increasing costs. Although modular construction has been widely applied to low-rise buildings, application in high-rise buildings remains limited, less than 1% worldwide. The need for residential high-rise building applying modular construction in Indonesia becomes important. The interdependence between parties in modular projects is greater than in conventional methods. Unavailability of design guidelines hinders the construction industry in implementing modular technology. The purpose of this study is to analyze the critical success factors for modular construction of residential high-rise buildings applying risk-based management to improve project time performance. Forty-one Indicators were drawn from literature reviews and specialist interviews to conduct a sustainability evaluation. The survey was submitted to case project developers, designers, supervisors, and contractors in Indonesia, thereafter statistically analyzed using SPSS and risk management analysis with three stages: risk sources, risk drivers and risk causes. Critical success factors for drawing approvals have a considerable influence on modular construction among 15 other factors, followed by supply chain and design standardization. It is necessary to mitigate these risks to improve project time performance.